LEVEL ADOPTION OF SOCIAL MEDIA AS AN MARKETING TOOLS OF SMALL MEDIUM ENTERPRISES PRODUCTS(CASE STUDY ON THE PARTICIPANTS OF IKM ALUMNI IN SURABAYA INDUSTRIAL TRAINING CENTER IN 2012) - Evi Septiana Pane (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2014)
SMEs as one pillar of the national economy received significant attention by government. One focus of the development of SMEs by the government is increasing mastery in the information technology area. Development of information technology in the field of marketing products on the internet, especially through Social Media, the government (institution builder SMEs) is necessary to determine first the level of Social Media utilization by SMEs in reality. Thus, both government and SMEs could determine the most appropriate action that meet their needs. The study was conducted by filling out the questionnaire by 105 SMEs in the graduate participant at Industrial Training Surabaya. As a result, found there are 4 levels of SMEs in the Social Media utilization as a tool to market products over the internet.Keywords : Marketing through Social Media, internet marketing for SMEs products, SMEs levels of Social Media utilization.